Endogenous oils derived from human adipocytes are potent adjuvants that promote IL-1 alpha-dependent inflammation. - O'FARRELLY, CLIONA; LAVELLE, EDWARD; CAMPBELL, MATTHEW; MOK, KENNETH (My University, 2014)
Obesity is characterized by chronic inflammation associated with neutrophil and M1 macrophage infiltration into white adipose tissue. However, the mechanisms underlying this process remain largely unknown. Based on the ability of oil-based adjuvants to induce immune responses, we hypothesized that endogenous oils derived from necrotic adipocytes may function as an immunological "danger signal." Here we show that endogenous oils of human origin are potent adjuvants, enhancing antibody responses to a level comparable to Freund's incomplete adjuvant. The endogenous oils were capable of promoting interleukin (IL)-1α-dependent recruitment of neutrophils and M1-like macrophages, while simultaneously diminishing M2-like macrophages. We found that endogenous oils from subcutaneous and omental adipocytes, and from healthy and unhealthy obese individuals, promoted comparable inflammatory responses. Furthermore, we also confirmed that white adipocytes in visceral fat of metabolically unhealthy obese (MUO) individuals are significantly larger than those in metabolically healthy obese individuals. Since adipocyte size is positively correlated with adipocyte death, we propose that endogenous oils have a higher propensity to be released from hypertrophied visceral fat in MUO individuals and that this is the key factor in driving inflammation. In summary, this study shows that adipocytes contain a potent oil adjuvant which drives IL-1α-dependent proinflammatory responses in vivo.
PUBLISHED
Keywords: diabetes; Cancer; Immunology, Inflammation & Infection